WILD EDIBLE PLANTS IN ENHANCING POST-DISASTER FOOD SECURITY, ORMOC CITY, PHILIPPINES - Patricia Anne Nazareno; Prof Ricardo Bagarinao; Inocencio Jr. Buot; Cindy Ochavillo (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights: - Wild edible plants (WEPs) in Ormoc City, Philippines, serve as critical food sources during disasters, offering essential nutrients and aiding food security. - Melastoma malabathricum is rich in calcium, magnesium, and manganese, while Diplazium esculentum provides high levels of iron, copper, and zinc. - Wild fruits like Melastoma malabathricum, Annona montana, and Rubus fraxinifolius contribute significant Vitamin C to the local diet. - These plants not only provide sustenance but also offer medicinal benefits, emphasizing the need for further research, conservation, and sustainable use.